Continuously varied infill pattern (ConVIP): improvement of mechanical properties and printing speed of fused filament fabrication (FFF) 3D printing - Sanglae Kim; Alberto Andreu; Insup Kim; Jeong-Hwan Kim; Jiho Lee; Yong-Jin Yoon (Journal of Materials Research and Technology, 2022)
The low mechanical properties and printing speed of fused filament fabrication (FFF) have remained important barriers to their widespread adoption in the industry. This study focused on the proposal of a layer stacking scheme that increases mechanical properties and reduces printing time through a continuously varied Infill Pattern (ConVIP). The ConVIP method showed a 15.2% and 40% increases in ultimate tensile strength, and elongation at break, compared to the conventional infill pattern within polylactic acid (PLA) filament. In addition, printing speed had been increased by 29.37% at most which was calculated through the length of the extruder path in G-Code. The results and relationship of process parameter was explained and analyzed through confocal microscopy. Overall, ConVIP represents an effective way to increase mechanical properties and reduce the printing speed of FFF printed parts without external processes. This method has transformed the discrete stacking process into a distributed process, and software enhancements can increase the possibility of FFF 3D printing through continuous variation of new process parameters.